2013
DOI: 10.4049/jimmunol.1203312
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Promotes Functional Responses in Inflammatory and Steady-State Dendritic Cells through Differential Requirement for Activation Function-1 of Estrogen Receptor α

Abstract: 17β-Estradiol (E2) has been shown to regulate GM-CSF– or Flt3 ligand–driven dendritic cell (DC) development through estrogen receptor (ER) α signaling in myeloid progenitors. ERα regulates transcription of target genes through two distinct activation functions (AFs), AF-1 and AF-2, whose respective involvement varies in a cell type– or tissue-specific manner. In this study, we investigated the role of ERα AFs in the development and effector functions of inflammatory DCs, steady-state conventional DCs, and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 62 publications
7
87
0
Order By: Relevance
“…Our data adds to previous reports on the influence of sex on production of IFNα by pDCs, demonstrating that also surface maturation markers are upregulated more in female pDCs (Berghöfer et al, 2006;Meier et al, 2009;Seillet et al, 2012Seillet et al, , 2013. The effect of sex on upregulation of especially CD40 but also CD86 was respectively mostly or partially explained by the rs179008 variant allele.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our data adds to previous reports on the influence of sex on production of IFNα by pDCs, demonstrating that also surface maturation markers are upregulated more in female pDCs (Berghöfer et al, 2006;Meier et al, 2009;Seillet et al, 2012Seillet et al, , 2013. The effect of sex on upregulation of especially CD40 but also CD86 was respectively mostly or partially explained by the rs179008 variant allele.…”
Section: Discussionsupporting
confidence: 74%
“…Although previous studies found no evidence for incomplete or skewed X-inactivation this was recently challenged by Souyris and colleagues who reported that pDC express more TLR7 in females due to escape of X-inactivation (Schott et al, 2007a;Berghöfer et al, 2006;Souyris et al, 2018). Besides, TLR7 function may be enhanced by female hormones and/or enhanced expression of molecules downstream of TLR7 (Seillet et al, 2012(Seillet et al, , 2013Griesbeck et al, 2015). It remains unclear why possession of a heterozygous genotype offers an advantage when it comes to pDC maturation and reducing CHB risk.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The female sex hormone estrogen is a good candidate for explaining the better TLR-mediated responses of human pDCs developing in female HuMice (19,20). Because estrogens mediate their effects through binding to the nuclear ERa and ERb, we examined the ER isotype expression profile of peripheral blood leukocytes including pDCs by quantitative PCR.…”
Section: Cell-intrinsic Er Signaling Potentiates the Tlr7 Responses Omentioning
confidence: 99%
“…We recently tested the hypothesis that the abundance of the female sex hormone estrogens may regulate TLR responsiveness of pDCs (19,20). We first showed that pDCs from postmenopausal women exhibited a reduced TLR-mediated response as compared with premenopausal women.…”
mentioning
confidence: 99%